Perfis etários, posição na ocupação e desigualdade de rendimentos no Brasil - Ramos, Lauro; Rios-Neto, Eduardo; Wajnman, Simone (Nova Economia, 2013)
Perfis etários, posição na ocupação e desigualdade de rendimentos no Brasil